Isotopic biosignatures in carbonate‐rich, cyanobacteria‐dominated microbial mats of the Cariboo Plateau, B.C. Issue 5 (14th August 2013) - Brady, A. L.; Druschel, G.; Leoni, L.; Lim, D. S. S.; Slater, G. F.
Abstract: Photosynthetic activity in carbonate‐rich benthic microbial mats located in saline, alkaline lakes on the Cariboo Plateau, B.C. resulted in p CO2 below equilibrium and δ 13 CDIC values up to +6.0‰ above predicted carbon dioxide (CO2 ) equilibrium values, representing a biosignature of photosynthesis. Mat‐associated δ 13 Ccarb values ranged from ~4 to 8‰ within any individual lake, with observations of both enrichments (up to 3.8‰) and depletions (up to 11.6‰) relative to the concurrent dissolved inorganic carbon (DIC). Seasonal and annual variations in δ 13 C values reflected the balance between photosynthetic 13 C‐enrichment and heterotrophic inputs of 13 C‐depleted DIC. Mat microelectrode profiles identified oxic zones where δ 13 Ccarb was within 0.2‰ of surface DIC overlying anoxic zones associated with sulphate reduction where δ 13 Ccarb was depleted by up to 5‰ relative to surface DIC reflecting inputs of 13 C‐depleted DIC. δ 13 C values of sulphate reducing bacteria biomarker phospholipid fatty acids (PLFA) were depleted relative to the bulk organic matter by ~4‰, consistent with heterotrophic synthesis, while the majority of PLFA had larger offsets consistent with autotrophy. Mean δ 13 Corg values ranged from −18.7 ± 0.1 to −25.3 ± 1.0‰ with mean Δ 13 Cinorg‐org values ranging from 21.1 to 24.2‰, consistent with non‐CO2 ‐limited photosynthesis, suggesting that Precambrian δ 13 Corg values of ~−26‰ do not necessitate higher atmospheric CO2 concentrations. Rather, it is likely that the high DIC and carbonate content of these systems provide a non‐limiting carbon source allowing for expression of large photosynthetic offsets, in contrast to the smaller offsets observed in saline, organic‐rich and hot spring microbial mats.